Eksistensi Diri Selebgram dalam Membangun Personal Branding: Studi Deskriptif pada Selebgram Non-Selebritas di Kota Bandung - Adhea Mauna Fazriskia Fasa; Wahyu Utamidewi; Rastri Kusumaningrum (VISA: Journal of Vision and Ideas, 2024)
This research discusses the existence of non-celebrity celebrities in the city of Bandung in building personal branding via Instagram. The concept of one's own existence is closely related to the human desire to understand the meaning of life and it is believed that no individual or entity can provide an understanding of one's purpose in life. In this research, existence is seen from the perspective of society in using social media, with a focus on Instagram as a platform for building personal branding. This research aims to find out how non-celebrity celebrities in the city of Bandung form strong and sustainable personal branding through the use of Instagram. This research uses a constructivist paradigm with descriptive qualitative research methods. Data was collected through interviews, observation, documentation and literature study. Informants were selected using a purposive sampling method with the criteria of non-celebrity celebrities and followers in the city of Bandung. The results of this research show that non-celebrity celebrities in the city of Bandung use Instagram as a personal branding tool in forming their self-image, with different strategies from one celebrity to another